Current CT practice in Germany: Results and implications of a nationwide survey. Issue 90 (May 2017) - Schegerer, Alexander A.; Nagel, Hans-Dieter; Stamm, Georg; Adam, Gerhard; Brix, Gunnar
Abstract: Purpose: To assess patient doses and relative frequencies of standard CT examinations performed in Germany in 2013/14 as well as the effect of modern CT technology on patient exposure. Methods: All known CT facilities in Germany were requested to complete a questionnaire on the frequency of 34 examinations and the respective parameter settings used. Taking into account type-specific properties of each scanner, effective doses were estimated for each reported examination. The mean and the percentiles of the CT dose index, scan length, dose length product, and effective dose were determined for each type of examination. Results: According to the data provided for about 11% of all medical CT scanners operated in 2013/14, the effective dose was 4.6/5.9 mSv per scan/examination. The effective dose was significantly reduced by about 15% compared to the CT practice before 2010. Modern CT technology, such as tube current modulation and iterative image reconstruction reduced the effective dose significantly by 6% and 13%, respectively. The mean effective dose applied at scanners produced by different manufacturers differed by 25%, at maximum. Conclusion: Patient exposure was reduced substantially in recent years. There is, however, still a considerable potential for further dose reduction by adapting scan protocols to the medical purpose and by a consequent exploitation of modern CT technologies.